Peterson's Graduate programs in the Humanities, Arts and Social Sciences (Thomson Peterson's, 2006)
The six volumes of Peterson’s Annual Guides to Graduate Study, the only annually updated reference work of its kind, provide wide-ranging information on the graduate and professional programs offered by accredited colleges and universities in the United States and U.S. territories and those in Canada, Mexico, Europe, and Africa that are accredited by U.S. accrediting bodies. Books 2 through 6 are divided into sections that contain one or more directories devoted to individual programs in a particular field. Book 2 contains programs of study in humanities, the arts, and social sciences.